2020
DOI: 10.1186/s40309-020-0161-4
|View full text |Cite
|
Sign up to set email alerts
|

Whose knowledge, whose values? An empirical analysis of power in transdisciplinary sustainability research

Abstract: The participation of practitioners in transdisciplinary sustainability research has been heralded as a promising tool for producing 'robust' knowledge and engendering societal transformations. Although transdisciplinary approaches have been advanced as an effective avenue for generating knowledge positioned to question and transform an unsustainable status quo, the political and power dimensions inherent to such research have hardly been discussed. In this article, we scrutinise the constitution of participati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 65 publications
(119 reference statements)
0
42
0
Order By: Relevance
“…Furthermore, the transference of a dominant actor's power onto the process may lead to reproduction of an already dominant societal discourse or one that is politically desirable. To some extent, such settings emerge from conditions prescribed by the funding body of the PASE activity, resulting in limited accountability of the dominant groups [83]. This argument is in line with Bora and Hausendorf [41] who critiqued participatory science governance, and Stilgoe et al [31] who observed that outcomes may "not sufficiently challenge, and so serve to reinforce, incumbent power structures".…”
Section: Factors Limiting Successful Pase Implementationmentioning
confidence: 85%
See 3 more Smart Citations
“…Furthermore, the transference of a dominant actor's power onto the process may lead to reproduction of an already dominant societal discourse or one that is politically desirable. To some extent, such settings emerge from conditions prescribed by the funding body of the PASE activity, resulting in limited accountability of the dominant groups [83]. This argument is in line with Bora and Hausendorf [41] who critiqued participatory science governance, and Stilgoe et al [31] who observed that outcomes may "not sufficiently challenge, and so serve to reinforce, incumbent power structures".…”
Section: Factors Limiting Successful Pase Implementationmentioning
confidence: 85%
“…Fritz and Binder [83] discuss the dimensions of politics and power inherent to transdisciplinary sustainability research. Differentiating between instrumental, structural, and discursive power, the authors uncover how funding bodies, researchers, and practitioners exert power over participatory processes, and how this limits participation in STI governance.…”
Section: Summary Of Contributions: International Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful transdisciplinary endeavours are those that foster reciprocal relations among disciplines and nondisciplinary participants, through accounting for and balancing power relations (Toomey et al, 2015). A meta-analysis study (Fritz & Binder, 2020) in five transdisciplinary projects in Germany found that the researchers commonly exercise instrumental power over the elements of participation, while practitioners and donor agencies exert structural and discursive power.…”
mentioning
confidence: 99%